2016
DOI: 10.3847/0004-637x/819/2/108
|View full text |Cite
|
Sign up to set email alerts
|

Compact Binary Merger Rates: Comparison With Ligo/Virgo Upper Limits

Abstract: We compare evolutionary predictions of double compact object merger rate densities with initial and forthcoming LIGO/Virgo upper limits. We find that: (i) Due to the cosmological reach of advanced detectors, current conversion methods of population synthesis predictions into merger rate densities are insufficient. (ii) Our optimistic models are a factor of 18 below the initial LIGO/Virgo upper limits for BH-BH systems, indicating that a modest increase in observational sensitivity (by a factor of ∼2.5) may bri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
281
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(298 citation statements)
references
References 150 publications
(310 reference statements)
15
281
1
1
Order By: Relevance
“…If the stars start too close, they may merge before both black holes are formed. In addition, the core collapse that forms a black hole can impart a kick of tens of km s −1 or more to the hole (see, e.g., [111,112] for recent discussions), which might unbind the binary.…”
Section: Isolated Binariesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the stars start too close, they may merge before both black holes are formed. In addition, the core collapse that forms a black hole can impart a kick of tens of km s −1 or more to the hole (see, e.g., [111,112] for recent discussions), which might unbind the binary.…”
Section: Isolated Binariesmentioning
confidence: 99%
“…These effects are incorporated in parameterized ways in various binary population synthesis codes (e.g., [113,114,115,111]; see [116] for a recent discussion of the evolution of compact binaries). The simulators are in a difficult position because massive stars are rare, and because some of the key phases of the evolution are extremely tough to observe, which means that there is reliance on our often-incomplete theoretical understanding of the relevant processes.…”
Section: Isolated Binariesmentioning
confidence: 99%
“…Spera et al, oelbert@uci.edu 2015; Belczynski et al, 2010, and references therein), and have been predicted to dominate the LIGO signal (e.g. Belczynski et al, 2016b). However, the possibility that the GW150914 event was due to primordial black holes (that would constitute some part of the dark matter) has also been advanced Cholis et al, 2016;Carr et al, 2016;Inomata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lamberts et al (2016) concluded that the black holes involved in GW150914 likely formed in a massive galaxy at z ∼ 1, but that formation in a dwarf galaxy was also likely possible. Belczynski et al (2016b) suggested that the black holes likely form in low-metallicity systems. Chatterjee et al (2017) explored the formation of BBH systems specifically in globular clusters and came to qualitatively similar conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…These discoveries verified earlier predictions that: (i) the first detection would happen when LIGO sensitivity reaches d nsns = 50-100 Mpc, that (ii) BH-BH mergers would dominate the gravitational-wave signal, and that (iii) the merging black holes would be substantially more massive than typical 10 M ⊙ A&A proofs: manuscript no. ms Galactic BHs (Belczynski et al 2010b;Dominik et al 2015;Belczynski et al 2016b).…”
Section: Introductionmentioning
confidence: 99%